THE FUNCTIONS OF EUPHEMISM IN UZBEK LANGUAGE (ON THE EXAMPLE OF O’TKIR HOSHIMOV’S SHORT STORIES) - Xujanazarova Xosiyat; Shoira Yusupova Batirovna (American Journals Publishing, 2023)
There is a rising tendency to avoid speaking directly about sensitive topics in the increasingly complicated, globalised society. Naturally, human being are tend to hear positive feedback rather than negative one. This article is focused on the functions of euphemism in the short stories entitled “ Hayollarga bo’laman tutqun”, “ Urushning so’nggi qurboni” , and “ O’zbeklar” written by O’tkir Hoshimov with the concept of the functions of euphemism in speech acts. The research is conducted by descriptive qualitative method related to social phenomena, in this case the uses of euphemism either in a literary or social text.
Keywords: euphemism, politeness, softening function, veiling function, communicative function, corrective function, conceptual meaning, positive attitude